REALISASI KESANTUNAN BERBAHASA DAN CITRA RAHMATAN LIL ALAMIN PADA WACANA KHOTBAH JUMAT: STUDI PRAGMATIK - Abdul Mukhlis; Muhammad Alghiffary; Heru Susanto (Kajian Linguistik dan Sastra, 2022)
The discourse of Friday sermons produced by the preachers is always interesting to study. Thediscourse has a pragmatic power that can influence the congregation to behave and act, bothpositive or negative though. Based on that, this study has two objectives, (1) to find out anddescribe the pattern of realization of language politeness that appears in the Friday sermondiscourse at mosques affiliated with Nahdlatul Ulama, Muhammadiyah, and Al-Irsyad massorganizations, (2) to reveal the implications between Friday sermon politeness and the characterof Islam which is rahmatan lil 'alamin. This research is descriptive qualitative research using apragmatic theory approach and Geoffrey Leech's language politeness device. The results of thisstudy include (1) the maxim of politeness data used by the preacher in Friday sermon discoursesin three mosques, among others, using the maxims of wisdom, generosity, praise, sympathy,consideration, and agreement. (2) The image of Islam that is Rahmatan Lil Alamin in thisresearch is reflected through polite utterances that are persuasive towards goodness. Thecharacter of Islam Rahmatan Lil Alamin that is found and realized in the polite speech includes,among other things, a fair, moderate attitude, and mutual love for fellow human beings.Keywords: language politeness, sermon discourse, pragmatic, Rahmatan Lil Alamin